EFEKTIVITAS TERAPI INFARED DAN LOW LEVEL LASER THERAPHY TERHADAP PASIEN NYERI PUNGGUNG BAWAH - Sheila Putri Mahardika; Muhammad Siddik; Didik Dwi Santoyo; Bambang Dwiputranto; Pagan Pambudi (Homeostasis, 2022)
Low back pain (LBP) is the most common complaint of low back pain. One of the treatments that can be done is non-pharmacological therapy, namely therapy IR and low level laser therapy (LLLT). Both have similarities in electromagnetic radiation hyperthermia, and serve to reduce pain severity, reduce disability in low back pain patients. The aim of this literature review is to compare the effectiveness of IR and LLLT in reducing pain in low back pain patients. The writing was done by analyzing the literature from several electronic medical journal databases, namely: PubMed-NCBI, ProQuest, Science Direct and Google Scholar. The criteria for inclusion of articles are articles in English and Indonesian in research published in 2011–2021. There are 5 articles used in this literature review. The results of the review found that IR and LLLT were equally effective in reducing pain in low back pain patients. Three out of five IR articles showed more effective results in reducing low back pain. Two of the five articles of LLLT showed more effective results in reducing low back pain, that IR and LLLT have the same effectiveness in reducing low back pain